2018
DOI: 10.1080/17461391.2018.1535626
|View full text |Cite
|
Sign up to set email alerts
|

The influence of physical exercise on the relation between the phase of cardiac cycle and shooting accuracy in biathlon

Abstract: This study examined the influence of physical exercise on the relation between shooting accuracy and the phase of the cardiac cycle in which the shot is fired. Thirteen experienced biathletes (8 females, mean age 17 years) fired from the standing position at rest and right after a submaximal exercise on a bicycle ergometer. Shooting accuracy and the timing of each shot relative to the R-waves of the electrocardiogram (ECG) were recorded. Best shots (with greatest accuracy) and worst shots (with lowest accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 45 publications
2
11
1
Order By: Relevance
“…These results are somewhat in line with Helin et al [ 44 ] in novice rifle shooters, who showed a random triggering within the cardiac cycle. In contrast, results differ from a study in junior-level biathletes [ 45 ], who showed an increased likelihood of triggering the shot in the middle and at the end of the cardiac cycle, during diastole. However, it should be considered that, in biathlon, triggering within the cardiac cycle may play a much higher role due to the preceding cross-country skiing condition, which means that biathletes may already be able to control triggering within the cardiac cycle at a lower skill level.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results are somewhat in line with Helin et al [ 44 ] in novice rifle shooters, who showed a random triggering within the cardiac cycle. In contrast, results differ from a study in junior-level biathletes [ 45 ], who showed an increased likelihood of triggering the shot in the middle and at the end of the cardiac cycle, during diastole. However, it should be considered that, in biathlon, triggering within the cardiac cycle may play a much higher role due to the preceding cross-country skiing condition, which means that biathletes may already be able to control triggering within the cardiac cycle at a lower skill level.…”
Section: Discussioncontrasting
confidence: 99%
“…In studies within novice air-rifle athletes, location of triggering within the cardiac cycle was correlated with shot score [ 27 ] but no correlation was found in junior-level air-rifle shooters [ 28 ]. These results are similar to Gallicchio et al [ 45 ] in junior-level biathletes, and Helin et al [ 44 ] in novices, who both showed a higher shot score when triggering during diastole. Results indicate that location of triggering may affect shot score in novice air-rifle athletes but may be independent of shot score in junior-level air-rifle shooters.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in the descriptive results it is possible to notice the fact that increasing intensity of the physical load corresponds with increased movement of the rifle, respectively worse rifle stability. Consequently, the increased heart rate correlates with worse targeting stability as has been confirmed in previous researches of several authors (Gallicchio et al, 2018;Haug, 2018;Ihalainen et al, 2018;Laaksonen et al, 2018;Sattlecker et al, 2015;Sattlecker et al, 2017;Vonheim, 2012;Žák et al, 2017). In our study, the statistical significance was only showed in comparing parameters of dynamics rifle stability during targeting in resting conditions against these parameters in exercise Intensity 3 in the women group.…”
Section: Discussionsupporting
confidence: 64%
“…The majority of researches that have been presented so far were chiefly focused on the stability of the standing shooting position, the stability of the rifle during targeting, triggering and the dependence of the above mentioned parameters on the shooting success (Gallicchio et al, 2018;Haug, 2018;Ihalainen et al, 2018;Laaksonen et al, 2018;Sattlecker et al, 2015;Sattlecker et al 2017;Žák et al, 2017). Results of specific researches confirmed the dependence between the intensity of the physical load and the athlete´s postural stability in the standing shooting position, especially in anterior-posterior axis (Gallicchio et al, 2018;Haug, 2018;Ihalainen et al, 2018;Laaksonen et al, 2018;Sattlecker et al, 2015;Sattlecker et al, 2017;Vonheim, 2012;Žák et al, 2017). Høydal and Nord (2017) presented the importance of heart rate monitors during training by junior biathletes.…”
Section: Introductionmentioning
confidence: 99%
“…Gallicchio et al 6 examined the relationship between shooting accuracy and the phase of the cardiac cycle in which the shot is fired. The researchers recorded shooting accuracy and timing of each shot relative to electrocardiogram R-waves.…”
Section: Discussionmentioning
confidence: 99%